Identification of Li+ binding sites and the effect of Li+ treatment on phospholipid composition in human neuroblastoma cells: a 7Li and 31P NMR study - Layden, Brian T. (2005)
Li+ binding in subcellular fractions of human neuroblastoma SH-SY5Y cells was investigated using 7Li NMR spin-lattice (T1) and spin-spin (T2) relaxation measurements, as the T1/T2 ratio is a sensitive parameter of Li+ binding. The majority of Li+ binding occurred in the plasma membrane, microsomes, and nuclear membrane fractions as demonstrated by the Li+ binding constants and the values of the T1/T2 ratios, which were drastically larger than those observed in the cytosol, nuclei, and mitochondria. We also investigated by 31P NMR spectroscopy the effects of chronic Li+ treatment for 4-6 weeks on the phospholipid composition of the plasma membrane and the cell homogenate and found that the levels of phosphatidylinositol and phosphatidylserine were significantly increased and decreased, respectively, in both fractions. From these observations, we propose that Li+ binding occurs predominantly to membrane domains, and that chronic Li+ treatment alters the phospholipid composition at these membrane sites. These findings support those from clinical studies that have indicated that Li+ treatment of bipolar patients results in irregularities in Li+ binding and phospholipid metabolism. Implications of our observations on putative mechanisms of Li+ action, including the cell membrane abnormality, the inositol depletion and the G-protein hypotheses, are discussed.